Performance study of frequency-hopped spread-spectrum system over composite effects of interference and fading - Jacquelyn (2016)
Frequency-hopped spread-spectrum systems have been known to provide benefits against signal interference, and would therefore be a good approach to improving signal transmission and reception. In this project, MATLAB simulation was used to study the bit-error rate performance of basic FSK signaling in different channel models. The bit-error rate performance of frequency-hopped spread-spectrum systems was also studied. This study will prove useful for future applications where interference is best at minimum, especially in defense systems.